Imprecise vowel articulation as a potential early marker of Parkinson's disease: effect of speaking task - Rusz, Jan; Cmejla, Roman; Tykalova, Tereza; Ruzickova, Hana; Klempir, Jiri; Majerova, Veronika; Picmausova, Jana; Roth, Jan; Ruzicka, Evzen (The Journal of the Acoustical Society of America, 2013)
The purpose of this study was to analyze vowel articulation across various speaking tasks in a group of 20 early Parkinson's disease (PD) individuals prior to pharmacotherapy. Vowels were extracted from sustained phonation, sentence repetition, reading passage, and monologue. Acoustic analysis was based upon measures of the first (F1) and second (F2) formant of the vowels /a/, /i/, and /u/, vowel space area (VSA), F2i/F2u and vowel articulation index (VAI). Parkinsonian speakers manifested abnormalities in vowel articulation across F2u, VSA, F2i/F2u, and VAI in all speaking tasks except sustained phonation, compared to 15 age-matched healthy control participants. Findings suggest that sustained phonation is an inappropriate task to investigate vowel articulation in early PD. In contrast, monologue was the most sensitive in differentiating between controls and PD patients, with classification accuracy up to 80%. Measurements of vowel articulation were able to capture even minor abnormalities in speech of PD patients with no perceptible dysarthria. In conclusion, impaired vowel articulation may be considered as a possible early marker of PD. A certain type of speaking task can exert significant influence on vowel articulation. Specifically, complex tasks such as monologue are more likely to elicit articulatory deficits in parkinsonian speech, compared to other speaking tasks.
Keywords: akustika; akustika řeči; Humans; Acoustics; Case-Control Studies; Sound Spectrography; lidé středního věku; měření tvorby řeči; časná diagnóza; studie případů a kontrol; Speech Acoustics; Predictive Value of Tests; Speech Perception; fonetika; Speech Production Measurement; Aged; dospělí; percepce řeči; kvalita hlasu; Phonetics; poruchy artikulace; Articulation Disorders; senioři; lidé; srozumitelnost řeči; časové faktory; Adult; Speech Intelligibility; fonace; Male; Middle Aged; prediktivní hodnota testů; Voice Quality; Aged, 80 and over; Early Diagnosis; senioři nad 80 let; zvuková spektrografie; mužské pohlaví; Parkinson Disease; Time Factors; Phonation; Parkinsonova nemoc